Pengaruh Promosi dan Inovasi Produk Terhadap Kinerja Pemasaran Melalui Citra Merek Pada UMKM Pakaian Muslimah di Kota Makassar - Ummu Kalsum Rahim R; Oesman Lewangka; Andi Mappatompo (Jurnal Ilmiah Multidisiplin Amsir, 2023)
This study aims to examine the effect of promotion and product innovation on marketing performance through brand image in Muslim clothing SMEs in Makassar City. The research was carried out at the Akhwat Sewing House in Makassar City using a quantitative approach. The sampling technique used is simple random sampling and produces 114 samples. The analysis technique used in this study is path analysis with the SEM-PLS method. The results of the study show that promotion has a positive and significant effect on brand image indicating that effective promotion can increase consumer positive perceptions of the brands offered. Product innovation has a positive and significant effect on brand image so that it is able to present innovative products from competitors. Promotion has a positive and significant effect on marketing performance so that it can increase consumer awareness of their products. Product innovation has no significant effect on marketing performance which indicates that other factors besides product innovation may be more dominant in influencing the marketing performance of these MSMEs. Brand image has a positive and significant effect on marketing performance which contributes to building consumer loyalty to the product. This study also found that brand image is able to mediate promotion on marketing performance, which means that good promotion will enhance brand image and contribute to marketing performance. Brand image is also able to mediate product innovation on marketing performance. Innovative products can build a positive brand image and enhance their marketing performance. This research recommends that MSMEs develop more effective and targeted promotion strategies, unique innovative products, and strengthen their brand image.